Structure of single KL0–, double KL1–, and triple KL2 − ionization in Mg, Al, and Si targets induced by photons, and their absorption spectra. (May 2022) - Ménesguen, Y.; Lépy, M.-C.; Ito, Y.; Yamashita, M.; Fukushima, S.; Tochio, T.; Polasik, M.; Słabkowska, K.; Syrocki, Ł.; Indelicato, P.; Gomilsek, J.P.; Marques, J.P.; et al.
Abstract: We investigated experimentally and theoretically x-ray properties of Mg, Al and Si to assess for new reliable x-ray useful quantities. We measured the KL 0 – diagram, and KL 1 – and KL 2 – satellite lines in Mg, Al, and Si, ionized by photon excitation, using a high-resolution anti-parallel double-crystal x-ray spectrometer. Their energy values, full width at half maxima (FWHM), and relative intensities are obtained by the multiple fitting methods and compared with those reported by other excitation processes. It was found that the relative intensity of Mg and Si KL 1 and KL 2 satellite lines to the KL 0 diagram lines depend on the method used to produce the K hole. The evidence of a new transition between Kα 3 and Kα 4 in Mg, Al, and S KL 1 satellite lines is suggested. These x-ray diagram and satellite lines were investigated theoretically and we found that Mg Kα 1, 2 diagram lines with hidden satellites are especially in very good agreement with the corresponding experimental ones. Moreover, we also determined the mass attenuation coefficients in a wide energy range covering the K -absorption edge, including a detailed evaluation of the associated uncertainties. From the absorption spectra of Mg and Al, the cross sections of the multi-electron transition processes were estimated and match the theoretical values. Highlights: High-resolution spectra of the Kα lines of Mg, Al and Si and their satellites. New theoretical values for the Kα lines of Mg, Al and Si and their satellites. Experimental mass attenuation coefficients for Mg, Al and Si on a wide energy range. Multi-electrons transition probabilities.